(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Loan classification is one of the most decisive elements of modern bank management because it influences asset quality assessment, provisioning policy, capital efficiency, and the overall sustainability of profit generation. In Uzbekistan, this issue is especially important because credit operations remain the dominant source of bank income and a major component of bank assets. The national legal framework defines the institutional basis of banking activity, while the Central Bank’s prudential rules require commercial banks to classify assets and form reserves for expected losses. However, a purely formal approach to classification does not fully reveal the real economic quality of a loan. A credit asset may appear profitable in nominal terms and still produce weak or unstable net returns once funding costs, monitoring costs, and expected losses are taken into account. This thesis argues that improving loan classification should be understood not only as a compliance requirement, but as a strategic instrument for protecting and increasing bank profitability. The paper uses official legal and statistical sources from Uzbekistan to show that more analytical and multi-layer classification improves the quality of profit, strengthens risk detection, and supports long-term portfolio efficiency.